The volatility of capital flows to emerging markets and financial services trade - Roland Beck (Goethe University Frankfurt, Center for Financial Studies (CFS), 2000)
This paper examines empirically the question whether the presence of foreign banks and a liberal trade regime with regard to financial services can contribute to a stabilization of capital flows to emerging markets. Since foreign banks, so the argument goes, provide better information to foreign investors and increase transparency, the danger of herding is reduced. Previous findings by Kono and Schuknecht (1998) confirmed empirically that such an effect does exist. This study expands their data set with respect to the length of the time period and the number of countries. Contrary to Kono and Schuknecht, it is found that foreign bank penetration tends to rather increase the volatility of capital flows. The trade regime variables are not significant in explaining cross-country variations in the volatility of capital flows. This result does not change significantly when alternative measures of volatility are considered.
urn:nbn:de:hebis:30-9751
Keywords: F13; F30; G20; 330; Financial Services Trade; Capital Flows